2022
DOI: 10.3390/sym14091775
|View full text |Cite
|
Sign up to set email alerts
|

Lagrangian Zero Truncated Poisson Distribution: Properties Regression Model and Applications

Abstract: In this paper, we construct a new Lagrangian discrete distribution, named the Lagrangian zero truncated Poisson distribution (LZTPD). It can be presented as a generalization of the zero truncated Poissson distribution (ZTPD) and an alternative to the intervened Poisson distribution (IPD), which was elaborated for modelling both over-dispersed and under-dispersed count datasets. The mathematical aspects of the LZTPD are thoroughly investigated, and its connection to other discrete distributions is crucially obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…This leads to the development of zero-truncated models, such as zero-truncated Poisson distribution [6] and zero-truncated Negative Binomial distribution [7]. Most recently introduced are the Zero-truncated negative binomial-Erlang distribution [8], a zero-truncated distribution [9] and Lagrangian Zero-truncated Poisson Distribution [10] among others.…”
Section: Original Research Articlementioning
confidence: 99%
“…This leads to the development of zero-truncated models, such as zero-truncated Poisson distribution [6] and zero-truncated Negative Binomial distribution [7]. Most recently introduced are the Zero-truncated negative binomial-Erlang distribution [8], a zero-truncated distribution [9] and Lagrangian Zero-truncated Poisson Distribution [10] among others.…”
Section: Original Research Articlementioning
confidence: 99%
“…Furthermore, the authors in [18] also used the LD 2 to create the generalized LKD of type two. The competence of the distributions proposed based on the LD 2 profoundly attracted our team, and as a result, we suggested the Lagrangian version of the ZTPD, the zero-truncated binomial distribution, and the IPD (see [26][27][28]). Moreover, the authors in [24] demonstrated that every member of the LD 2 was also a member of the LD 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the authors in [16] discussed the methods for generating different classes of Lagrangian probability distributions. Our team was very impressed by the competency of the distributions proposed based on the Lagrangian method, and as a result, we proposed the Lagrangian version of ZTPD through the work published in [17]. Furthermore, the authors in [18] concentrated on the Lagrangian approach's construction of the zero-truncated binomial distribution (ZTBD) and explained how effective it was in comparison to other zero-truncated distributions.…”
Section: Introductionmentioning
confidence: 99%